VD_FINDINFO Jug / 2014 / 192 vom 5. Februar 2014 - VD Tribunal cantonal (2014)
LOI FÉDÉRALE SUR LES ARMES, LES ACCESSOIRES D'ARMES ET LES MUNITIONS, INDEMNITÉEN GÉNÉRAL | 4 al. 1 let. d LArm, 429 CPP (CH)